1998
DOI: 10.1046/j.1365-201x.1998.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased pulmonary vascular resistance during nasal breathing: modulation by endogenous nitric oxide from the paranasal sinuses

Abstract: Nitric oxide is present in high concentration in the human nasal airways. During inspiration through the nose a bolus is transported to the lungs. In a randomized cross-over study the effect of two different patterns of breathing, nasal breathing and mouth breathing, was evaluated in 10 patients (mean age 65 years), breathing room air the morning of the first post-operative day after open heart surgery. Nasal breathing is defined as inspiration through the nose and expiration through the mouth, whilst mouth br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 14 publications
(15 reference statements)
4
23
0
Order By: Relevance
“…Consistent with this hypothesis, impaired pulmonary NO synthesis in iNOS-/-mice is associated with augmented hypoxia-induced pulmonary hypertension [20], and aerosol-mediated iNOS gene transfer in the bronchial tree of rats attenuates hypoxic pulmonary hypertension [21]. In humans, pulmonary artery pressure is lower during nasal than during oral breathing [22], and impaired lower respiratory tract NO production is associated with exaggerated hypoxic pulmonary vasoconstriction [23]. Taken together, these data are consistent with the concept that NO derived from the respiratory tract participates in the regulation of pulmonary artery pressure.…”
Section: Discussionsupporting
confidence: 61%
“…Consistent with this hypothesis, impaired pulmonary NO synthesis in iNOS-/-mice is associated with augmented hypoxia-induced pulmonary hypertension [20], and aerosol-mediated iNOS gene transfer in the bronchial tree of rats attenuates hypoxic pulmonary hypertension [21]. In humans, pulmonary artery pressure is lower during nasal than during oral breathing [22], and impaired lower respiratory tract NO production is associated with exaggerated hypoxic pulmonary vasoconstriction [23]. Taken together, these data are consistent with the concept that NO derived from the respiratory tract participates in the regulation of pulmonary artery pressure.…”
Section: Discussionsupporting
confidence: 61%
“…There is evidence in humans, that in addition to pulmonary endothelial, respiratory epithelial NO also regulates pulmonary artery pressure [ 18 ]. In line with this hypothesis, we and others found that alveolar epithelial NO synthesis (as evidenced by lower respiratory tract exhaled NO) is defective in HAPE-prone subjects [ 19 , 20 ].…”
Section: Short-term Cardiovascular Adaptation To Hypoxiasupporting
confidence: 61%
“…Two recent studies found a trend towards better gas exchange with partial elimination or diversion of endogenous NO production. SETTERGREN et al [42] eliminated the autoinhalation of nasal and sinus NO in humans and FAGAN et al [43] abolished endothelial cell production of NO in a knockout mouse deficient in endothelial NOS. These findings strongly suggest the intriguing possibility that endogenous basal NO production in the lung or upper respiratory tract does not serve the purpose of regulating V '/Q '.…”
Section: Differences Between Effects Of Nmentioning
confidence: 99%